The Influence of The Tea Party Cooperative Learning Model on History Subjects on The Learning Activity of Class XI Students of Abulyatama Private High School - Fadilla, *Fatimah Sara; Umar, Mawardi; Haikal, Muhammad (Universitas Syiah Kuala, 2021)
This study aims to determine the effect of the tea party cooperative learning model on history subjects on the learning activities of class XI students of Abulyatama Private High School. The background in this study is the lack of active students because the learning process only focuses on forming discussion groups and also lectures that can provoke boredom from students. This study uses a qualitative approach and the type of descriptive research. The subjects selected in this study were class XI IPA 1, which consisted of 20 people. The collection technique used is observation. While the data analysis technique is qualitative data analysis. Based on the results of the study, it was obtained data that the tea party cooperative learning model in history subjects had an effect on the learning activity of class XI students of Abulyatama Private High School, this was evidenced by an observation sheet that included the percentage of student learning activity in the learning process. Students' learning activity during the learning process using the tea party type cooperative learning model got a percentage of 92.5% with an increase from the previous observation of 47.5 %.